Analysis of external costs of CO2 emissions for CNG buses in intercity bus service - Ivković, Ivan; Kaplanović, Snežana; Sekulić, Dragan (Transport, 2019)
Within the transport sector, road transport is the largest source of Carbon Dioxide (CO2) emissions. Greater use of vehicles that run on clean alternative fuels can contribute to reduce CO2 emissions. This paper gives special attention to the Compressed Natural Gas (CNG) buses and their comparison with conventional diesel buses, which in countries such as Serbia have a dominant share. Justification of using CNG buses in order to mitigate climate changes is measured by realised annual and average external costs of CO2 emissions. These external costs provide a basis for future use of economic instruments by which negative impacts of transport on the environment can be limited. Research of CO2 emissions and external costs of CO2 emissions in intercity bus service was conducted for three technical-technological concepts of CNG buses in comparison to the two types of conventional diesel buses. Analysis was carried out according to four various scenarios that define different operating conditions on the road network of the Serbia. Obtained results show that CNG buses reduce annual external costs of CO2 emissions by 2…24% compared to conventional diesel buses. Obtained average external costs of CO2 emissions per 100 bus-kms show to what extent their changes are a result of changes of external costs of CO2 emissions and to what extent they are due to changes of operating conditions on the road network.